Targeted Capture and Next-Generation Sequencing Identifies C9orf75, Encoding Taperin, as the Mutated Gene in Nonsyndromic Deafness DFNB79 - Rehman, Atteeq Ur (Elsevier, 2010)
Targeted genome capture combined with next-generation sequencing was used to analyze 2.9 Mb of the DFNB79 interval on chromosome 9q34.3, which includes 108 candidate genes. Genomic DNA from an affected member of a consanguineous family segregating recessive, nonsyndromic hearing loss was used to make a library of fragments covering the DFNB79 linkage interval defined by genetic analyses of four pedigrees. Homozygosity for eight previously unreported variants in transcribed sequences was detected by evaluating a library of 402,554 sequencing reads and was later confirmed by Sanger sequencing. Of these variants, six were determined to be polymorphisms in the Pakistani population, and one was in a noncoding gene that was subsequently excluded genetically from the DFNB79 linkage interval. The remaining variant was a nonsense mutation in a predicted gene, C9orf75, renamed TPRN. Evaluation of the other three DFNB79-linked families identified three additional frameshift mutations, for a total of four truncating alleles of this gene. Although TPRN is expressed in many tissues, immunolocalization of the protein product in the mouse cochlea shows prominent expression in the taper region of hair cell stereocilia. Consequently, we named the protein taperin.